A systems design study on Child Jesus College - Bautista, Maria Carmina F.; Delmendo, Bryan Dexter H.; Doliro, Glen Mark V.; Malapad, Leandro (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Due to the disaccreditation of Child Jesus College from CHED, a problem in the school's systems was detected. However, from further investigation, the problems of Child Jesus College were found to be much more deeply rooted into the school's entire system even without the seemingly unsatisfactory college program. Thus, a total systems design study was conducted in order to determine the root causes of the faults in Child Jesus College's system. The college department was excluded from the study in order to prioritize the analysis on the school's current system which has its own issues to begin with. A structured documentation and analysis was initially performed. From there the school was found to have a decreasing trend in the entire student population since 2010 where the student population experienced an anomalous spike from the previous year and has continued to decrease ever since. This opposed the school's external environment wherein the population trend of Caloocan City had an average annual population growth rate of 2.37% from 2000 to 2010. Furthermore, Child Jesus College is located in barangay 176 which was the most populous of all the 188 barangays in Caloocan City. Thus, internal factors that contributed to the schools decreasing enrollment rates and instances of student dropouts were identified and used in the study's systems analysis and problem analysis. The systems analysis of the entire system also determined other weaknesses that were present in Child Jesus College's management, utilization of facilities, teacher evaluation measures, and marketing strategies. On the other hand, a problem analysis was conducted as well to determine the root causes of Child Jesus College's low profit for the past years. The issues brought from the systems analysis and problem analysis were then integrated and grouped into four main categories: performance management, facilities and layout planning, marketing plan, and managerial accounting and financial planning. From these four main categories, recommendations were made for each of the weaknesses and root causes in order to design the proposed system. The study then described how management can use these recommendations to transform into an efficient and effective organization. The study culminated with the estimated benefits, of these recommendations, to Child Jesus College.
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial systems design.
Keywords: Private schools -- Philippines; System analysis